SIS 2017. Statistics and Data Science: new challenges, new generations Proceedings of the Conference of the Italian Statistical Society, Florence 28-30 June 2017 - Petrucci, Alessandra; VERDE, Rosanna (Proceedings e report, 2017)
The 2017 SIS Conference aims to highlight the crucial role of the Statistics in Data Science. In this new domain of 'meaning' extracted from the data, the increasing amount of produced and available data in databases, nowadays, has brought new challenges. That involves different fields of statistics, machine learning, information and computer science, optimization, pattern recognition. These afford together a considerable contribute in the analysis of 'Big data', open data, relational and complex data, structured and no-structured. The interest is to collect the contributes which provide from the different domains of Statistics, in the high dimensional data quality validation, sampling extraction, dimensional reduction, pattern selection, data modelling, testing hypotheses and confirming conclusions drawn from the data.